Transient heat stress irreversibly disrupts molecular signals, cellular and developmental competence of riverine buffaloes (Bubalus bubalis) oocytes and early embryos in a stage-specific manner - Devender Singh; Parul Sarwalia; Manish Kumar; Moloya Gohain; Asit Jain; Tripti Jain; Rakesh Kumar; Tirtha Kumar Datta (Molecular Biology Reports, 2026)

Correction: The hidden architects of the genome: a comprehensive review of R-loops - Chetna Yadav; Ritu Yadav; Smiti Nanda; Shalu Ranga; Parul Ahuja (Molecular Biology Reports, 2026)

Therapeutic potential of an ethnoveterinary formulation against Staphylococcus aureus–induced mastitis via modulating TLR-2/NOX-2 pathway - M. Ratheesh; Svenia P. Jose; S. Sheethal; S. Sandya; Parul Dhar; Deeksha Pandit (Journal of Molecular Histology, 2026)

First report on black spot of rose (Rosa indica L.) caused by Colletotrichum siamense from India - Moitreyee Das; Phanindra P V; Parul; Priyanshu Gupta; Shyam Saran Vaish (Physiological and Molecular Plant Pathology, 2026)

Life-cycle and techno-economic analyses of agro-waste-derived biodegradable plastics enhanced via AI-based parametric optimization - Abhishek Kumar Singh; Md Monjurul Islam; Parul Sharma; Anmol Sharma; Sankha Chakrabortty; Riti Kumari; Sayantan Sarkar; Moonis Ali Khan; Ramesh Kumar; Byong-Hun Jeon (Environmental Research, 2026)

Rhizosphere microbial population and their plant growth-promoting functionality are influenced by soil sodicity and crop diversity - Pooja Verma; Priyanka Chandra; Arvind Kumar Rai; Nirmalendu Basak; Kailash Prajapat; Ram Kishor Fagodiya; Parul Sundha; Baljeet Singh Saharan; Rajender Kumar Yadav (Soil and Tillage Research, 2026)

Optimizing water retention and nutrient release in soil with diammonium phosphate-loaded guar gum/diatomite composite hydrogel: Implications for agriculture - Poonam BARALA; Parul SANGWAN; Jyoti YADAV; Vinita HOODA (Pedosphere, 2026)

Effect of biopolymers and proteins-based microencapsulation on stability and water solubility of temple waste (Tagetes erecta) derived carotenoids - Nivedita Thakur; Sarvpreet Singh; Parul; Pamita Bhandari (Food Chemistry, 2026)

Documentation of indigenous knowledge of medicinal plants of Jaunsari’s living in Dehradun, India for sustainable preservation - Parul Gangwar; M. S. Karuna (Plant Biosystems, 2026)

Deciphering the resurrection response of cyanobacterium, Brasilonema sp. to desiccation and rehydration via NMR-based metabolomics and oxidative stress profiling - Parul Sharma; Shuvasish Choudhury; Jayashree Rout (Algal Research, 2026)

Next-generation biodegradation of chlorpyrifos: integrative microbial strategies, molecular mechanisms, and environmental impacts - Sushma Gautam; Jyoti Sharma; Monu Sharma; Sonu Sharma; Raman Kumar; Vivek Sheel; Parul Gautam; Ahmad Umar; Abdulrab Ahmed M. Alkhanjaf; Ahmed A. Ibrahim; Sotirios Baskoutas (Biodegradation, 2026)

A Holistic Review of Jimson Weed (Datura Stramonium): Addressing Past Challenges and Future Advancements - Anita Sharma; Shyna Bhalla; Kritika Saini; Parul Dhar; Priyanka Mahajan (Journal of Crop Health, 2026)

Elucidating Climate Change-induced Heat Stress on the Physico-chemical and Antioxidant Attributes of Heirloom Mango Varieties - Swosti Suvadarsini Das; Thukkaram Damodaran; Anshuman Singh; Vishambhar Dayal; Ashish Yadav; Amar Kant Kushwaha; Ningthoujam Samarendra Singh; Dheerendra Rastogi; Parul Sagar (Tropical Plant Biology, 2026)

Photocatalytic degradation of methylene red dye using biosynthesized silica coated semiconductor photocatalyst - M A Ashwini; Yashneeti Mehta; Anita Gupta; Kumar Rakesh Ranjan; Maumita Das Mukherjee; Parul Khurana; Sheenam Thatai (Next Research, 2026)

Fourier transform infrared spectroscopy to evaluate the photo-stability and acid degradation behavior of indinavir sulphate: A sustainable approach in pharmaceutical analysis - Aparna Shekhar; Umesh Kumar; Meenu Sarbhai; Sobinder Singh; Parul Singh; Ranjana Mehrotra (Next Research, 2026)

Effects of rice residue mulch and irrigation scheduling on wheat yield and water productivity in north-west India - Parul Mandal; V. K. Sindhu; A. S. Brar (Irrigation Science, 2026)

Computational design and immunoinformatic validation of a multistage mRNA vaccine candidate against Mycobacterium tuberculosis - Manika Sharma; Parul Bhatt; Medha Singh; Kiran Bharat Lokhande; Shailendra Asthana; Monika Sharma; Sadhna Sharma (In Silico Pharmacology, 2026)

Augmenting the Elemental Sulphur–based Formulation with Pseudomonas Chloritidismutans Strain WH2 for Improved Sodic Soil Reclamation and Crop Performance - Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Harshpreet Kaur; Sandeep Bedwal; Subedar Patel; Sanjay Kumar; Rameshwar Lal Meena; Parbodh Chander Sharma; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Integrative Morphological and Molecular Characterization of Steinernema Siamkayai Isolates from Semi-Arid India and Their Prospects for Biological Control - Ayushi Chaudhary; Istkhar Rao; Parul Chauhan; Aashaq Hussain Bhat; Ashish Kumar Singh (Journal of Crop Health, 2026)

Effect of biopolymer stabilization on fly ash: correlating unconfined compressive strength with small strain shear modulus - Parul Rawat; Amit Kumar Ram; Supriya Mohanty (Innovative Infrastructure Solutions, 2026)

Genotypic characterization on the basis of chilling requirement in apple (Malus × domestica Borkh.) using simple sequence repeat (SSR) markers - Madhuri Tiwari; Rajnish Sharma; Megha Sharma; Poonam; Anamika Thakur; Parul Sharma; Pramod Verma; Anupama Singh (Genetic Resources and Crop Evolution, 2026)

Synthesis of Diosgenin by Pseudomonas aeruginosa D3, an Endophyte of Dioscorea bulbifera - Krishna Nanda Dhal; Pramod Kumar Sahu; Amrita Gupta; Adarsh Kumar; Zaryab Shafi; Parul Johri; Sushma Mishra; Alok Kumar Srivastava (Current Microbiology, 2026)

Towards a context-aware framework for cellular senescence - Arnab Nath; Parul Mehrotra; Chiranjib Bhattacharyya; Deepak Kumar Saini (Biogerontology, 2026)

Optimisation and utilization of deep eutectic solvents for the green extraction of anticancer alkaloids from Catharanthus roseus - Avjot Kaur; Ramandeep Kaur; Urvashi Bhardwaj; Parul Sharma (Natural Product Research, 2026)

Effects of bisphenol A and bisphenol S on human fallopian tube contractions: An in vitro and in silico study - Richa Singh; Parul Sharma; Sakshi Agarwal; Shristi Modanwal; Sushmitha Paulraj; Sanjeev Kumar Mahto (Reproductive Toxicology, 2026)

Isolation and characterization of the thermotolerant bacterial symbiont Xenorhabdus stockiae from Steinernema siamkayai, collected from the semi-arid region of Rajasthan, India - Parul Chauhan; Istkhar Rao; Sakshi Singh (International Journal of Tropical Insect Science, 2026)

Cost-effective mitigation strategies for air quality management in Uttar Pradesh, India - Pallav Purohit; Wolfgang Schöpp; Parul Srivastava; Fabian Wagner; Zbigniew Klimont; Gregor Kiesewetter; Sagnik Dey; Jostein Nygard; Ashish Tiwari; Mukesh Sharma; Markus Amann; Adriana Gomez-Sanabria; et al. (Journal of Environmental Management, 2026)

An integrated approach towards utilizing bittern for chemicals recovery: Technoeconomic and sustainability analysis - Barnabas Gao; Parul Sahu; Kirti M. Yenkie (Journal of Cleaner Production, 2026)

Corrigendum to “Nutrient removal and biomass production of marine microalgae cultured in recirculating aquaculture systems (RAS) water with low phosphate concentration” [J. Environ. Manag., Volume 358, May 2024, 120859] - Parul Jakhwal; Ehsan Daneshvar; Kinga Skalska; Leonidas Matsakas; Alok Patel; Yuri Park; Amit Bhatnagar (Journal of Environmental Management, 2026)

Evaluation of clinically approved neuroprotective drugs as adjunct therapies in experimental cerebral malaria - Prince Joshi; Salique Hassan Shaham; Rahul Shivahare; Kanchan Yadav; Anamika Sharma; Parul; Shubha Shukla; Renu Tripathi (Archives of Microbiology, 2026)

Role of the primary healthcare providers in sickle cell disease management: a scoping review - Parul Gazta; Janesh Gautam; Mahendra Thakor; Pankaj Bhardwaj; S. S. Mohanty (Journal of Community Genetics, 2026)

Meta-topolin as an effective cytokinin source to enhance in vitro establishment, shoot multiplication and alleviation of shoot tip necrosis (STN) in kiwiberry (Actinidia arguta) cultivars - Shakshi; Shehnaj Khan; Kritika Khagta; Parul Sharma; Chanchal Kumari; Shreya Narwal; Rajnish Sharma; Vishal Singh Rana (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Effect of Reclamation Approaches on the Soil Properties and Performance of the Rice-Wheat Cropping System Under Alkali Irrigation - Anu Sehrawat; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Parul Sundha; Sandeep Bedwal; Devvrat Dhiman; Mukesh Yadav; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Waste to Wealth: Acidulated Organic Manures for Enhanced Productivity and Nutrient–Supplying Capacity of Alkaline Soils - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Priyanka Chandra; Dev Raj; Anita Mann; Subedar Patel; Harspreet Kaur; Sanjay Kumar; Raksh Vir Jasra; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Molecular insights into glial neuroimmune cross reactivity with CNS antigens and its role in neuroinflammation - Anil Kumar Yadav; Priyanka Verma; Ashish Srivastava; Parul Srivastava; Rohit Rai; Shubham Rathour (Inflammopharmacology, 2026)

Mash 878: A New Variety of Kharif Urdbean for North West Plain Zone (NWPZ) - Ashok Kumar; R. K. Gill; Shayla Bindra; Parul Sharma; Inderjit Singh; Sarvjeet Singh (Indian Journal of Genetics and Plant Breeding, 2026)

Correction to: The interconnected battle: climate change, soil antibiotic microbial resistance, and human health - Saurabh Singh; Vivek Kumar; Parul Chaudhary; Vishal Tripathi; Ram Krishna; Waquar Akhter Ansari; Durgesh Kumar Jaiswal (Climatic Change, 2026)

The interconnected battle: climate change, soil antibiotic microbial resistance, and human health - Saurabh Singh; Vivek Kumar; Parul Chaudhary; Vishal Tripathi; Ram Krishna; Waquar Akhter Ansari; Durgesh Kumar Jaiswal (Climatic Change, 2026)

Boosting β-carotene in rice and wheat grains through seed-specific expression of a modified wheat or gene - Parul Sirohi; Ritika Vishnoi; Suchi Baliyan; Bidya Bhushan Gupta; Pratibha Demiwal; Hugo Germain; Debabrata Sircar; Harsh Chauhan (Transgenic Research, 2026)

Decomposition and entomofaunal succession pattern of burnt pig carcasses in a semi-arid part of India - Ravi Tanwar; Sapna Sharma; Parul Sharma; Tapeshwar Bhardwaj (International Journal of Tropical Insect Science, 2026)

Ultrasonic-assisted betalain extraction from red dragon fruit pulp (Hylocereus polyrhizus) using response surface methodology - Bhawna Chauhan; Parul Sharma; Davinder Pal Singh Oberoi (Food Chemistry, 2026)

Integrated biohydrogen and bioproduct generation from algal and food waste feedstocks: A techno-economic and environmental assessment - Christopher Selvam D; Yuvarajan Devarajan; Beemkumar Nagappan; Nakul Ramanna; Premananda Pradhan; Md Irfan Ahmed; Parul Bansal (Bioresource Technology Reports, 2026)

Trade-offs in sustainable crop diversification for climate resilience: soil health, emission reduction, and energy use in low-input systems - Tarun Kumar; Vijay Singh Meena; Alka Rani; Parul Chaudhary; Ramakrishna roy; Ratnesh Kumar Jha (Journal of Environmental Management, 2026)

Regional distribution and seasonal histomorphology of cell types of pars distalis adenohypophysis of Gaddi goats: A comparative study between the year 2001 and the present in the context of climate change - Arjun Kumar Rao; Virender Pathak; Rajesh Rajput; Divya Gupta; Parul Shukla (Tropical Animal Health and Production, 2026)

Hydrological Contributions of Snow and Glacier Melt from the Gangotri Glacier System and Their Climatic Controls Since 1980 - Parul Vinze; Ghulam Hussain; Smriti Srivastava; Mohd. Farooq Azam; Md. Arif Hussain; Umesh Haritashya (Journal of the Indian Society of Remote Sensing, 2026)

From stress to strength: Improving fenugreek seed germination under saline conditions with moringa leaf extract priming as a biostimulant approach - Ekta Pandey; Rinkee Kumari; Shahla Faizan; Parul Verma (Plant Science, 2025)

Nutrient removal, biomass accumulation, lipid production, and biostimulant activity of floating photosynthetic biofilm in synthetic wastewater - Parul Jakhwal; Ehsan Daneshvar; Amit Bhatnagar (Journal of Environmental Management, 2025)

Assessment of promoter methylation status and expression of lncRNA CASC2 in cervical cancer - Shalu Ranga; Ritu Yadav; Meenakshi B. Chauhan; Preeti Chauhan; Ravindresh Chhabra; Parul Ahuja (The Nucleus, 2025)

Modifications of RNA in cancer: a comprehensive review - Shalu Ranga; Ritu Yadav; Meenakshi Chauhan; Ravindresh Chhabra; Parul Ahuja; Nikita Balhara (Molecular Biology Reports, 2025)

Management strategies for stem rot of berseem caused by Sclerotinia sclerotiorum lib. De Bary using bio-based products - Parul Upadhyay; D. K. Banyal (Indian Phytopathology, 2025)

Six-membered N-heterocyclic alkaloids as ChE inhibitors in alzheimer’s disease treatment - Parul Yadav; Anchal Dabas; Ram Singh (Metabolic Brain Disease, 2025)

Biodegradation of the widely used amide herbicides: Microbial resources, catabolic pathways and molecular mechanisms - Guiling Si; Quanhong Zhang; Mingqiu Liu; Wen-Juan Chen; Yuting Tong; Parul Chaudhary; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Multivariable analysis of highly pathogenic H5N1 and H5Nx avian influenza in wild birds and poultry in Asian subregions - Hammed Olawale Fatoyinbo; Parul Tiwari; Ryan H.L. Ip; Victor Miranda (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Deterioration of agronomic traits and depletion of nutritional content in three varieties of wheat (Triticum aestivum L.) grown in arsenic contaminated soil - Sanika Jain; Jyoti Mathur; Parul Sharma; Chandra Kumari (Plant and Soil, 2025)

Enhancing rural well-being: A comprehensive analysis of housing design quality and typologies in india’s composite climate - Priya Tyagi; Parul Bhyan; Bhavna Shrivastava; Nand Kumar (Environment, Development and Sustainability, 2025)

HPLC-DAD quantification of mangiferin, antioxidant potential and essential oil composition of the leaves of five varieties of Mangifera indica L. of North India - Prakhar Saxena; Deepak Sharma; Parul Gautam; Abhishek Niranjan; Subha Rastogi (Natural Product Research, 2025)

A successful cultivation of Flammulina elastica , distantly related to the widely cultivated species F. filiformis - Anupam Barh; Manoj Nath; Babita Kumari; Parul Verma; Kirti Kaundal; Shweta Bijla; Monika Thakur; Shwet Kamal; Sudheer Kumar Annepu; Ved Parkash Sharma (New Zealand Journal of Botany, 2025)

Putrescine attenuates heat stress by modulating membrane stability, antioxidant activity, and gaseous exchange in Brassica juncea L. - Parul Sharma; Nita Lakra; Annu Luhach; Abbu Zaid; Kadambot H.M. Siddique (Plant Science, 2025)

Bioremediation of acetamiprid in contaminated environments: Microbial resources, metabolic pathways and enzymatic mechanisms - Xiaofang Luo; Mingqiu Liu; Haoran Song; Zeren Li; Parul Chaudhary; Saurabh Gangola; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2025)

Geospatial monitoring of peri-urban zones in Chandigarh through multi-year landsat imagery - Jyoti Saini; Umesh Kumar; Anil Kumar Gupta; Parul Mishra; Ratchagaraja Dhairiyasamy; Deekshant Varshney; Subhav Singh (Urban Ecosystems, 2025)

Germplasm characterization of commercial and wild gooseberry (Phyllanthus emblica L.) through physico-chemical and molecular attributes: useful insights for genetic resource management - Megha Sharma; Rajnish Sharma; Ashwini Zadokar; Anamika Thakur; Parul Sharma; Suresh Kumar (Genetic Resources and Crop Evolution, 2025)

Assessment of pea (Pisum sativum L.) and cauliflower (Brassica oleracea L. var. botrytis) productivity in Mulberry (Morus alba L.) based agroforestry system in mid-hills of the north-western Himalayas: effects of tree canopy, fertiliser and bio-stimulants - Parul Bhushan; D. R. Bhardwaj; Prashant Sharma; Rushal Dogra; Samriti Pathania; Dhirender Kumar (Agroforestry Systems, 2025)

Localization of mitochondria along axons and at synapses in C. elegans touch receptor neurons is necessary for touch habituation - Sneha Hegde; Nayantara Varma; Parul Sood; Sandhya P Koushika (Journal of Biosciences, 2025)

Biochemical composition, amino acid and fatty acid profile changes of aquaculture feeds formulated from alternative ingredients: Long duration, storage temperature effects and ancillary FTIR confirmation - Parul Puri; Jaigopal Sharma; Rina Chakrabarti; Guddu Kumar; Avanish Kumar Shrivastav; Ram Singh (Journal of Stored Products Research, 2025)

Optimization of densified paddy straw-based total mixed ration in form of briquette for sustainable livestock feeding - Parul Rana; Raman Malik; Harneet Kour; Amandeep Goyal; Kanwate Rishikesh (Journal of Cleaner Production, 2025)

Engineering single Pd atom in W18O49 nanowire for ultra-sensitive crop pest detection and remote data communication - Prem Kumar; Kanchan Swami; Nilakantha Tripathy; Rajashri R. Urkude; Ankita Dadhich; Parul Sharma; Manish Singh; Kesavan Subaharan; Abir De Sarkar; Vijayakumar Shanmugam (Chemical Engineering Journal, 2025)

Exploring different environmental impacts: How abiotic factors shape flavonoid synthesis in plants - Hurmat; Richa Shri; Parul Sood; Gagandeep Kaur (Biocatalysis and Agricultural Biotechnology, 2025)

De Novo Transcriptome Assembly, Novel EST-SSR Development, and Preliminary Genetic Analysis in Saussurea costus (Falc.) Lipsch, an Industrially Important Endangered Medicinal Herb of the North-Western Himalayas - Kamal Thakur; Rajnish Sharma; Parul Sharma; Anamika Thakur; Ashwini Zadokar; Vinay Kumar; Bhupender Dutt (Plant Molecular Biology Reporter, 2025)

YTHDC1 orchestrates oncogenic splicing via the CLK1-SRSF1 splicing machinery to regulate castration-resistant prostate cancer progression - Parth Gupta; Devesh Srivastava; Vinayak Nayak; B Vishal Rao; K. Suseela; Rakesh Sharma; Senthil J. Rajappa; T. Subramanyeshwar Rao; Parul Mishra; Ashish Misra (Molecular and Cellular Biochemistry, 2025)

Retraction Note: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2025)

Effect of dietary micronutrient supplementation on growth and reproductive parameters in bull calves - Parul Kuraichya; Prasanth M. Nair; Rashika Srivastava; Vaibhav Dhaigude; Parul Chaudhary; Mukesh Bhakat; Veena Mani; Goutam Mondal (Journal of Thermal Biology, 2025)

Groundwater Hydrogeochemistry, Regional Vulnerability and Trace Metal Enrichments Around Indus Basin Agricultural Fields of SE Punjab, India - Susanta Paikaray; Parul Singh; Shefali Chander; Alankrit Bhardwaj; Athiyarath Krishnan Sudheer; Sanjeev Kumar (Water, Air, & Soil Pollution, 2025)

Effects of Specific Micronutrients on Semen Quality and Reproductive Outcomes in Peripubertal Sahiwal Bulls - Vaibhav Dhaigude; Parul Chaudhary; Prasanth M. Nair; Hardik Naliyapara; Mukesh Bhakat; Goutam Mondal (Biological Trace Element Research, 2025)

Multi-component image analysis for citrus disease detection using convolutional neural networks - Parul Sharma; Pawanesh Abrol (Crop Protection, 2025)

Limited evidence of the effectiveness of antiviral drugs to prevent brain infection by SARS-COV-2 in the K18-hACE2 murine model - S. De Neck; J. Schläpfer; R. Penrice-Randal; S. Parul; E.G. Bentley; A. Kirby; F. Seehusen; J.P. Stewart; Anja Kipar (Journal of Comparative Pathology, 2025)

Developmental Stage Significantly Affects In Vitro Propagation Practices: A Case Study in Paris polyphylla Smith, an Important Endangered Medicinal Plant of Himalayas - Vinay Kumar; Rajnish Sharma; Parul Sharma; Yash Pal Sharma; Kamal Thakur; Reena Sharma (Journal of Plant Growth Regulation, 2025)

Acidulated composts govern the soil solution nutrient composition through changes in key functional bacterial community of alkaline soils - Sandeep Bedwal; Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Amresh Chaudhary; Harshpreet Kaur; Subedar Patel; Sanjay Kumar; Rajender Kumar Yadav (Applied Soil Ecology, 2025)

Graphical analysis of multi-environmental trials for rose scented geranium (Pelargonium graveleons L'H'er.L'Herit ex Ait) essential oil yield using GGE biplot analysis - Ashish Kumar; Nilesh Sharma; Anil Kumar Gupta; Anju Yadav; Parul Sharma; C.S. Chanotiya; R.K. Lal (Biochemical Systematics and Ecology, 2025)

Mitigating Salinity Stress in Crops using Talaromyces sp.: Impacts on Phosphorus Solubilization, Growth and P Nutrition - Priyanka Chandra; Arvind Kumar Rai; Nirmalendu Basak; Parul Sundha; Sandeep Bedwal; Kailash Prajapat; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2025)

Correction to: Isolation and characterization of novel lytic bacteriophages that infect multi drug resistant clinical strains of Escherichia coli - Sudhaker Padmesh; Aditi Singh; Sidharth Chopra; Manodeep Sen; Saman Habib; Deepti Shrivastava; Parul Johri (Environmental Science and Pollution Research, 2025)

Interplay between quantitative trait loci for stem strength and agronomic traits in a wheat doubled-haploid population - J. Allan Feurtado; Letitia M. Da Ros; Shola H. Kareem; Breenah Mulligan; Daiqing Huang; Lanette Ehman; Parul Jain; Leah K. Flatman; Hanna Hovland; Jeff Hovland; Brett Beckie; Richard D. Cuthbert; et al. (Field Crops Research, 2025)

Comment on Smart mining policy: Integrating fuzzy-VIKOR technique and the Z-number concept to implement industry 4.0 strategies in mining engineering (by Poormirzaee et al.) - Parul Tomar; Amit Kumar (Resources Policy, 2025)

Advances in photocatalytic hydrogen production with ZnO/ZnS-Based nanostructured materials - Parul Rana; Vatika Soni; Rohit Kumar; Sonu; Akshay Chawla; Aftab Aslam Parwaz Khan; Pardeep Singh; Sourbh Thakur; Pankaj Raizada; Khalid A. Alzahrani (Fuel, 2025)

MSMEG_5850, a global TetR family member supports Mycobacterium smegmatis to survive environmental stress - Parul Singh; Jagdeep Kaur (Folia Microbiologica, 2025)

ALR inhibits HBV replication and autophagosome formation by ameliorating HBV-induced ROS production in hepatic cells - Amit Kumar Mishra; Md. Musa Hossain; Teja Naveen Sata; Kishor Pant; Ajay K. Yadav; Amrendra Kumar Sah; Parul Gupta; Md Ismail; Baibaswata Nayak; Shalimar; Senthil Kumar Venugopal (Virus Genes, 2025)

Simple sequence repeats (SSRs)-based characterization of cultivated and indigenous wild pomegranates (Punica granatum L.) revealed evolutionary relationships with considerable insights to native resource exploration - Himanshu Pandey; Rajnish Sharma; Dinesh Singh Thakur; Maneet Rana; Parul Sharma (Journal of Plant Biochemistry and Biotechnology, 2025)

Stability of Anti-Drug Antibodies Against Antibody Therapeutics - Parul Sirohi; Kelly Hainline; Heather Bullock; Sihe Wang; Robert J. Konrad; Yi Wen (The AAPS Journal, 2025)
Biotherapeutics have the potential to elicit unwanted immune responses that can lead to the production of anti-drug antibodies (ADA). It is critical that ADA responses are detected, characterized, and monitored to understand the safety and efficacy of a drug. ADA samples must remain stable in long- and short-term storage conditions to ensure reliable analysis. Whereas the stability of anti-vaccine antibodies has been well-studied, there are few reports examining the stability of anti-therapeutic antibodies using clinical samples. In this study, ADA samples from four clinical trials of antibody therapeutics were found to be stable after long-term storage (1–10 years) at -80°C and short-term storage (24 h to two weeks) at 4°C, 22°C, and 37°C. In addition, samples were stable after 16 freeze/thaw cycles. The results demonstrate the stability of ADA in clinical samples under various conditions. Consequently, the results observed herein suggest that the routine assessment of ADA sample stability may not be warranted. Graphical Abstract

Evaluating statistical and machine learning techniques for sugarcane yield forecasting in the tarai region of North India - Anurag Satpathi; Neha Chand; Parul Setiya; Rajeev Ranjan; Ajeet Singh Nain; Dinesh Kumar Vishwakarma; Kashif Saleem; Ahmad J. Obaidullah; Krishna Kumar Yadav; Ozgur Kisi (Computers and Electronics in Agriculture, 2025)

Exploration of morphological diversity to select naturally occurring promising walnut (Juglans regia L.) genotypes from the North-Western Himalayan region - Umesh Sharma; Hari Paul Sankhyan; Vishal Singh Rana; Rajesh Sharma; Anita Kumari; Rajneesh Kumar; Parul Sharma; Balkrishna Tiwari; Shikha Thakur; Neeraj Sankhyan; Sunny Sharma; Shilpa Sharma (South African Journal of Botany, 2025)

Advancements and challenges in Fenton-based advanced oxidation processes for antibiotic removal in wastewater: From the laboratory to practical applications - Yunus Ahmed; Akser Alam Siddiqua Maya; Parul Akhtar; Hamad AlMohamadi; Abdul Wahab Mohammad; S.M. Ashekuzzaman; Agnieszka I. Olbert; Md Galal Uddin (Journal of Environmental Chemical Engineering, 2025)

Enhancing melatonin photostability and controlled release using pH-responsive mesoporous silica nanoparticles for agricultural applications - Parul Sangwan; Poonam Barala; Vinita Hooda (Biocatalysis and Agricultural Biotechnology, 2025)

Cranial nerve palsies in leprosy: a systematic review of published case reports and case series - Ravindra Kumar Garg; Parul Jain; Swastika Suvirya; Neeraj Kumar; Ravi Uniyal; Praveen Kumar Sharma (Acta Neurologica Belgica, 2025)

Microwave-Assisted Green Synthesis of Fluorescent Graphene Quantum Dots: Metal Sensing, Antioxidant Properties, and Biocompatibility Insights - Parul Singh; Hitasha Vithalani; Aditya Adhyapak; Tinodaishe Semwa; Nihal Singh; Mukesh Dhanka; Dhiraj Bhatia; Jhuma Saha (Journal of Fluorescence, 2025)

Corrigendum to “In vitro anticoagulant effects of Bungarus venoms on human plasma which are effectively neutralized by the PLA2-inhibitor varespladib” [Toxicon Volume 252, December 2024, 108178] - Abhinandan Chowdhury; Bryan G. Fry; Stephen P. Samuel; Ashish Bhalla; Sakthivel Vaiyapuri; Parul Bhargava; Rebecca W. Carter; Matthew R. Lewin (Toxicon, 2025)

Comprehensive insights on association mapping in perennial fruit crops breeding – Its implications, current status and future perspectives - Ashwini Zadokar; Parul Sharma; Rajnish Sharma (Plant Science, 2025)

Exploring environmental and managerial impacts of crude oil volatility on QUAD financial markets: Insights into dynamic connectedness - Miklesh Prasad Yadav; Neha Puri; Parul Bhatia; Adam P. Shore (Journal of Environmental Management, 2025)

In vitro anticoagulant effects of Bungarus venoms on human plasma which are effectively neutralized by the PLA2-inhibitor varespladib - Abhinandan Chowdhury; Bryan G. Fry; Stephen P. Samuel; Ashish Bhalla; Sakthivel Vaiyapuri; Parul Bhargava; Rebecca W. Carter; Matthew R. Lewin (Toxicon, 2024)

Synthesis of calcium sulfate whiskers via acidification exploiting FGD gypsum for improved binder properties - Aakriti; Soumitra Maiti; Neeraj Jain; Parul Prajapati (Sustainable Chemistry and Pharmacy, 2024)

Exploring the frontiers of carbon nanotube synthesis techniques and their potential applications in supercapacitors, gas sensing, and water purification - Mamta Bulla; Vinay Kumar; Raman Devi; Sunil Kumar; Rita Dahiya; Parul Singh; Ajay Kumar Mishra (Journal of Environmental Chemical Engineering, 2024)

Multi-omics analysis reveals the positive impact of differential chloroplast activity during in vitro regeneration of barley - Parul Sirohi; Chanderkant Chaudhary; Mayank Sharma; Ravi Bodampalli Anjanappa; Suchi Baliyan; Ritika Vishnoi; Sumit Kumar Mishra; Reeku Chaudhary; Bhairavnath Waghmode; Anuj Kumar Poonia; Hugo Germain; Debabrata Sircar; et al. (Plant Molecular Biology, 2024)

The hidden architects of the genome: a comprehensive review of R-loops - Chetna Yadav; Ritu Yadav; Smiti Nanda; Shalu Ranga; Parul Ahuja (Molecular Biology Reports, 2024)

Understanding the HPV associated cancers: A comprehensive review - Nikita Balhara; Ritu Yadav; Shalu Ranga; Parul Ahuja; Mukesh Tanwar (Molecular Biology Reports, 2024)

Use of discarded corneo-scleral rims to create cornea-like tissue - Maryada Sharma; Subhpreet Kaur; Nimisha A. Mavlankar; Alokananda Chanda; Parul Chawla Gupta; Uma Nahar Saikia; Jagat Ram; Asish Pal; Sanjay Mandal; Purnananda Guptasarma; Manni Luthra-Guptasarma (Molecular Biology Reports, 2024)

S2AM: a sustainable smart agriculture model for crop protection based on deep learning - Abhilasha Sharma; Parul Sharma (Journal of Plant Diseases and Protection, 2024)

Revolutionizing High Temperature Stress Relief: Exploring the Latest Advances in Salicylic Acid Application - Monika Janaagal; Parul Sharma; Gayatri Kumari; Heena Gulia; Gali Suresh; Sridevi Tallapragada; Sarita Devi; Nita Lakra; Sunder Singh Arya; Pooja Pooja (Journal of Crop Health, 2024)

Deployment of intelligent irrigation monitoring system with Android app for machine learning prediction - Parul Taneja; Ashish Pandey (Environmental Monitoring and Assessment, 2024)

A novel interpretable machine learning and metaheuristic-based protocol to predict and optimize ciprofloxacin antibiotic adsorption with nano-adsorbent - Yunus Ahmed; Akser Alam Siddiqua Maya; Parul Akhtar; Md Shafiul Alam; Hamad AlMohamadi; Md Nurul Islam; Obaid A. Alharbi; Syed Masiur Rahman (Journal of Environmental Management, 2024)

Correction to: Conserving industrially important endangered medicinal herb Trillium govanianum (Himalayan Trillium) through biotechnological based interventions - Vinay Kumar; Garima; Rajnish Sharma; Aayushee Thakur; Parul Sharma; Yash Pal Sharma; Anamika Thakur; Sneh Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Physico-chemical characteristics and quality assessment of soil in parts of the Banganga Basin in northeastern Rajasthan, NW India - Asha Saxena; M. K. Pandit; Vijay Pal Meena; Rachit Parihar; Sarina Kalia; Parul Bairwa (Environmental Monitoring and Assessment, 2024)

Tailoring ZnS nanostructures through precipitation-cum-hydrothermal synthesis for enhanced wastewater purification and antibacterial treatment - Harpreet Kaur; Sanjeev Kumar; Parul Kumar; Ayman A. Ghfar; Gassoumi Bouzid (Environmental Research, 2024)

Conserving industrially important endangered medicinal herb Trillium govanianum (Himalayan Trillium) through biotechnological based interventions - Vinay Kumar; Garima; Rajnish Sharma; Aayushee Thakur; Parul Sharma; Yash Pal Sharma; Anamika Thakur; Sneh Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Pharmacological insights and role of bufalin (bufadienolides) in inflammation modulation: a narrative review - Gagandeep Kaur; Sushma Devi; Akhil Sharma; Parul Sood (Inflammopharmacology, 2024)

Comparative evaluation of statistical and machine learning models for weather-driven wheat yield forecasting across different districts of Punjab - Kulwinder Kaur Gill; Kavita Bhatt; Akansha; Parul Setiya; Sandeep Singh Sandhu; Baljeet Kaur (Arabian Journal of Geosciences, 2024)

Optical Chemosensor as a Sensitive and Selective Tool for the Detection of Thiocyanate Ions Via Cu2+ Induced Sensor and Its Practical Application - Parul Bhalla; Rajesh Malhotra (Journal of Fluorescence, 2024)

Visualization of synergistic interaction between inorganic nanoparticle and bioinoculants - Bharti Kukreti; Parul Chaudhary; Anita Sharma (Vegetos, 2024)

Genetic structure and gene flow among populations of willow (Salix species) - Anchal; Jai Pal Sharma; Tushal; Sapna Thakur; Parul Sharma; Anamika Thakur (Ecological Genetics and Genomics, 2024)

Decoding the chemical repertoire, antimicrobial synergy, and antioxidant mastery of banana pulp and peel extracts - Parul Narwal; Bhuvnesh Kapoor; Neelam Prabha Negi (Journal of Plant Biochemistry and Biotechnology, 2024)

Isolation and Characterization of Extended-Spectrum β-Lactamase Producing Escherichia coli from Pig Farms and Slaughterhouse - Jagana Niharika; Rajib Deb; Ranjeet Parihar; Priyanka Kumari Thakur; Pranav Anjaria; Gyanendra Singh Sengar; Parul Chaudhary; Seema Rani Pegu; Nitin Attupurum; Naveena Antony; Swaraj Rajkhowa; Vivek Kumar Gupta (Indian Journal of Microbiology, 2024)

A topological review on protein–protein interactions: the development and promises in the era of omics - Ananya Kapoor; Sourjadeep Mondal; Anubha Chaudhary; Swati Sharma; Parul Mehra; Amit Prasad (Journal of Proteins and Proteomics, 2024)

Improved Z-number based fuzzy fault tree approach to analyze health and safety risks in surface mines by I. M., Jiskani, F., Yasli, S., Hosseini, A. U., Rehman, S., Uddin [Resources Policy 76 (2022) 102591]: Suggested modification - Parul Tomar; Amit Kumar (Resources Policy, 2024)

Harnessing neural network model with optimization for enhanced ciprofloxacin antibiotic adsorption from contaminated water: A transparent and objective framework - Yunus Ahmed; Md. Mahfujur Rahman; Md Shafiul Alam; Mohammad Islam Miah; Md. Shamimul Haque Choudhury; Obaid A. Alharbi; Parul Akhtar; Syed Masiur Rahman (Journal of Water Process Engineering, 2024)

5,7-dihydroxy-3′,4′,5′-trimethoxyflavone mitigates lead induced neurotoxicity in rats via its chelating, antioxidant, anti-inflammatory and monoaminergic properties - Varinder Singh; Richa Shri; Parul Sood; Manjinder Singh; Thakur Gurjeet Singh; Ravinder Singh; Amit Kumar; Sheikh F. Ahmad (Food and Chemical Toxicology, 2024)

Heat-stress-responsive HvHSFA2e gene regulates the heat and drought tolerance in barley through modulation of phytohormone and secondary metabolic pathways - Sumit Kumar Mishra; Chanderkant Chaudhary; Suchi Baliyan; Anuj Kumar Poonia; Parul Sirohi; Meenakshi Kanwar; Snehi Gazal; Annu Kumari; Debabrata Sircar; Hugo Germain; Harsh Chauhan (Plant Cell Reports, 2024)

Assessment of higher demand of household energy consumption in different households in India: an inter-comparative study and solar savings valuation - Abhishek Saxena; Atul A. Sagade; Erdem Cuce; Desh Bandhu Singh; Avnish Kumar; Parul Gupta (Environmental Science and Pollution Research, 2024)

Geochemical fractionation, bioavailability, and ascertaining ecological risk of phosphorus in surface and core sediments of mangroves, western coast of India - Parul Maurya; Rina Kumari; Jigar Kumar B. Solanki; Rajesh Kumar Ranjan (Environmental Science and Pollution Research, 2024)

Exploring the phytochemistry and biological potential of Tagetes minuta (L.): A comprehensive review - Nitin Verma; Namita Aggarwal; Parul Sood (South African Journal of Botany, 2024)

Nutrient removal and biomass production of marine microalgae cultured in recirculating aquaculture systems (RAS) water with low phosphate concentration - Parul Jakhwal; Ehsan Daneshvar; Kinga Skalska; Leonidas Matsakas; Alok Patel; Yuri Park; Amit Bhatnagar (Journal of Environmental Management, 2024)

Vascular changes in association with non-suppurative encephalitis in SARS-CoV-2-infected K18-hACE2 mice - S. De Neck; U. Hetzel; S. Parul; E.G. Bentley; A. Kirby; F. Seehusen; J.P. Stewart; A. Kipar (Journal of Comparative Pathology, 2024)

The resurgence of old material: The impact of boehmite-derived catalytic material on the formation of dihydropyran compounds and its application to access fragrant derivatives - Manas Barik; Brijesh Patel; Shilpa Dabas; Parul Rathour; Dharm S. Padariya; Lakhya Jyoti Konwar; Atul Kumar; Rajendra Srivastava; Palani S. Subramanian; Saravanan Subramanian (Chemical Engineering Journal, 2024)

Forecasting soybean yield: a comparative study of neural networks, principal component analysis and penalized regression models using weather variables - Yunish Khan; Vinod Kumar; Parul Setiya; Anurag Satpathi (Theoretical and Applied Climatology, 2024)

Evaluating the performance of Grid IMD, NASA POWER, and MarkSim timeseries weather dataset for Uttarakhand Climatic Condition - Parul Setiya; Manjari Singh; Ajeet Singh Nain (Theoretical and Applied Climatology, 2024)

A review on fluoride contamination in groundwater and human health implications and its remediation: A sustainable approaches - Pankaj Kumar; Manoj Kumar; Abdulwasa Bakr Barnawi; Parul Maurya; Snigdha Singh; Deepankshi Shah; Virendra Kumar Yadav; Anand Kumar; Ramesh Kumar; Krishna Kumar Yadav; Amel Gacem; Akil Ahmad; et al. (Environmental Toxicology and Pharmacology, 2024)

The Emerging Role of Toll-Like Receptor-Mediated Neuroinflammatory Signals in Psychiatric Disorders and Acquired Epilepsy - Anubha Chaudhary; Parul Mehra; Anand K Keshri; Suraj S Rawat; Amit Mishra; Amit Prasad (Molecular Neurobiology, 2024)

“Long COVID” and Its Impact on The Environment: Emerging Concerns and Perspectives - Parul Rana; Shilpa Patial; Vatika Soni; Pardeep Singh; Atul Khosla; Sourbh Thakur; Chaudhery Mustansar Hussaisn; Patricia de Carvalho Nagliate; Lucas Meili; Rangabhashiyam Selvasembian; Pankaj Raizada (Environmental Management, 2024)

Bacillus subtilis strain BS87 as a biocontrol agent against spot blotch disease: effect on growth, nutrient status, and antioxidant enzymes in wheat - Priyanka Chandra; Rinki Khobra; Parul Sundha; Amaresh Chandra; Rakesh Kumar Sharma; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2024)

Impact of synbiotics on growth performance and gut health in Murrah buffalo calves - Amit N Sharma; Parul Chaudhary; Chand Ram Grover; Sachin Kumar; Goutam Mondal (Veterinary Research Communications, 2024)

Correction: A novel plant disease diagnosis framework by integrating semi-supervised and ensemble learning - Parul Sharma; Abhilasha Sharma (Journal of Plant Diseases and Protection, 2024)

A novel plant disease diagnosis framework by integrating semi-supervised and ensemble learning - Parul Sharma; Abhilasha Sharma (Journal of Plant Diseases and Protection, 2024)

Effect of Vivipary and Excessive Heat Unit Accumulation on JelIy Seed Disorder in Mango (Mangifera indica L.) - Israr Ahmad; Parul Sagar; Ashish Yadav; Amar Kant Kushwaha; Vinod Kumar Singh; Dinesh Kumar (Applied Fruit Science, 2024)

Isolation, characterization and management of endophyte(s) prevailing during the in vitro establishment of endangered medicinal herb Himalayan Trillium (Trillium govanianum Wall. ex D. Don) - Damini Chaudhary; Vinay Kumar; Rajnish Sharma; Sunita Devi; Parul Sharma; Pankaj Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Mapping of understorey invasive plant species clusters of Lantana camara and Chromolaena odorata using airborne hyperspectral remote sensing - Bodi Surya Pratap Chandra Kishore; Amit Kumar; Purabi Saikia; Nikhil Lele; Parul Srivastava; Sandeep Pulla; Hebbalalu Suresh; Bimal Kumar Bhattarcharya; Mohammed Latif Khan; Raman Sukumar (Advances in Space Research, 2024)

Retrieval of crop biophysical-biochemical variables from airborne AVIRIS-NG data using hybrid inversion of PROSAIL-D - Jayachandra Ravi; Rahul Nigam; Bimal K. Bhattacharya; Devansh Desai; Parul Patel (Advances in Space Research, 2024)

A review on hospital wastewater treatment technologies: Current management practices and future prospects - Geeta Bhandari; Parul Chaudhary; Saurabh Gangola; Sanjay Gupta; Ashulekha Gupta; Mohd Rafatullah; Shaohua Chen (Journal of Water Process Engineering, 2023)

Darjeeling tea profiling using 1H NMR and multivariate analysis - Kavitha Rachineni; Vrushali Siddesh Shirke; Parul Sharma; Kshitij Mishra; Mahendra S. Shirsath; Neeraj Praphulla Awasthi (Food and Humanity, 2023)

Converting waste to resource: Utilisation of elemental S and consortia of halo–alkaliphilic S–oxidisers for preparation of acidified compost from organic wastes - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Subedar Patel; Dev Raj; Anita Mann; Sanjay Kumar; Priyanka Chandra; Rajender Kumar Yadav (Bioresource Technology Reports, 2023)

Systematic literature review of life cycle sustainability assessment system for residential buildings: using bibliometric analysis 2000–2020 - Parul Bhyan; Bhavna Shrivastava; Nand Kumar (Environment, Development and Sustainability, 2023)

Impact of zinc, copper, manganese and chromium supplementation on growth performance and blood metabolic profile of Sahiwal (Bos indicus) male calves - Prasanth M Nair; Rashika Srivastava; Parul Chaudhary; Parul Kuraichya; Vaibhav Dhaigude; H. B. Naliyapara; Goutam Mondal; Veena Mani (BioMetals, 2023)

A comprehensive review on the decabromodiphenyl ether (BDE-209)-induced male reproductive toxicity: Evidences from rodent studies - Debarshi Sarkar; Parul Midha; Shashanka Sekhar Shanti; Shio Kumar Singh (Science of The Total Environment, 2023)

Exploring genetic diversity and ascertaining genetic loci associated with important fruit quality traits in apple (Malus × domestica Borkh.) - Poonam; Rajnish Sharma; Parul Sharma; Naveen C. Sharma; Kuldeep Kumar; Krishna Nand Singh; Vinay Bhardwaj; Narender Negi; Neena Chauhan (Physiology and Molecular Biology of Plants, 2023)

Homocysteine and nutritional biomarkers in cognitive impairment - Bhargava Seema; K. Sethi Prahlad; Batra Anuradha; Choudhury Sangeeta; Takkar Parul; Manocha Anjali; Kankra Mamta; Singla Parul (Molecular and Cellular Biochemistry, 2023)

Insights into the Therapeutic Potential of Phytoconstituents as an Epigenetic Modulators in Diabetic Nephropathy - Komal Thapa; Heena Khan; Amarjot Kaur Grewal; Neha Kanojia; Gagandeep Kaur; Parul Sood; Thakur Gurjeet Singh (Current Pharmacology Reports, 2023)

Efficient decolourization of toluidine blue and methylene blue using Bacillus cereus - Shivani Singh; Parul Chaudhary; Anita Sharma (Vegetos, 2023)

From biomolecules to biogeochemistry: Exploring the interaction of an indigenous bacterium with gold - Santonu K. Sanyal; Tara Pukala; Parul Mittal; Frank Reith; Joël Brugger; Barbara Etschmann; Jeremiah Shuster (Chemosphere, 2023)

Comparative study of depotash vinasse and molasses as binder and production performance in lactating Murrah buffaloes - Gaurav Pratap Singh; Parul Chaudhary; Nitin Tyagi; Mukesh Bhakat; Goutam Mondal (Tropical Animal Health and Production, 2023)

Predicting rice yield based on weather variables using multiple linear, neural networks, and penalized regression models - Parul Setiya; Anurag Satpathi; Ajeet Singh Nain (Theoretical and Applied Climatology, 2023)

Correction to: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2023)

Correction to: Overview of genetic and epigenetic regulation of human papillomavirus and apoptosis in cervical cancer - Chetna Yadav; Ritu Yadav; Ravindresh Chhabra; Smiti Nanda; Shalu Ranga; Lokesh Kadian; Parul Ahuja (Apoptosis, 2023)

Chemical constituents, pharmacological activities, and uses of common ayurvedic medicinal plants: a future source of new drugs - Parul Kaushik; Priyanka Ahlawat; Kuldeep Singh; Raman Singh (Advances in Traditional Medicine, 2023)

Facile and rapid detection of adulteration in mustard oils: NMR and unsupervised machine learning - Kavitha Rachineni; Parul Sharma; Vrushali Siddesh Shirke; Kshitij Mishra; Neeraj Praphulla Awasthi (Food Control, 2023)

Zinc Acts Synergistically with Berberine for Enhancing Its Efficacy as an Anti-cancer Agent by Inducing Clusterin-Dependent Apoptosis in HT-29 Colorectal Cancer Cells - Sandip Nathani; Rutusmita Mishra; Parul Katiyar; Debabrata Sircar; Partha Roy (Biological Trace Element Research, 2023)

Long non-coding RNAs as critical regulators and novel targets in cervical cancer: current status and future perspectives - Shalu Ranga; Ritu Yadav; Ravindresh Chhabra; Meenakshi B. Chauhan; Mukesh Tanwar; Chetna Yadav; Lokesh Kadian; Parul Ahuja (Apoptosis, 2023)

Characterization of piggery farm waste-borne bacterial transposable elements associated with antimicrobial resistance phenotypes - Priyanka Kumari Thakur; Rajib Deb; Seema Rani Pegu; Ranjeet Parihar; Jagana Niharika; Pranab Jyoti Das; Gyanendra Singh Sengar; Joyshikh Sonowal; Parul Chaudhary; Arutkumaran Selvaradjou; Atul Raj; Vivek Kumar Gupta (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Nanoencapsulation of Docetaxel Induces Concurrent Apoptosis and Necroptosis in Human Oral Cancer Cells (SCC-9) via TNF-α/RIP1/RIP3 Pathway - Parul Gupta; Arpita Singh; Ajay Kumar Verma; Surya Kant; Anuj Kumar Pandey; Anupam Mishra; Puneet Khare; Ved Prakash (Indian Journal of Clinical Biochemistry, 2023)

Isolation and characterization of novel lytic bacteriophages that infect multi drug resistant clinical strains of Escherichia coli - Sudhaker Padmesh; Aditi Singh; Sidharth Chopra; Manodeep Sen; Saman Habib; Deepti Shrivastava; Parul Johri (Environmental Science and Pollution Research, 2023)

Morus alba fruit diet ameliorates cognitive deficit in mouse model of streptozotocin-induced memory impairment - Parul Sood; Varinder Singh; Richa Shri (Metabolic Brain Disease, 2023)

Overview of genetic and epigenetic regulation of human papillomavirus and apoptosis in cervical cancer - Chetna Yadav; Ritu Yadav; Ravindresh Chabbra; Smiti Nanda; Shalu Ranga; Lokesh Kadian; Parul Ahuja (Apoptosis, 2023)

Nanoparticle-mediated bioremediation as a powerful weapon in the removal of environmental pollutants - Parul Chaudhary; Lukman Ahamad; Anuj Chaudhary; Govind Kumar; Wen-Juan Chen; Shaohua Chen (Journal of Environmental Chemical Engineering, 2023)

Developing resistance against soil-borne Fusarium pathogen causing tomato wilt through in vitro cell line selection - Ishani Shaunak; Rajnish Sharma; Parul Sharma; Meenu Gupta; Ramesh Kumar Bhardwaj (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Review: Current understanding on biological filtration for the removal of microcystins - Youchul Jeon; Parul Baranwal; Lei Li; Kayla Piezer; Youngwoo Seo (Chemosphere, 2023)

Role of C-terminal domain of Mycobacterium tuberculosis PE6 (Rv0335c) protein in host mitochondrial stress and macrophage apoptosis - Medha; Priyanka; Parul Bhatt; Sadhna Sharma; Monika Sharma (Apoptosis, 2023)

Irrigation water quality, gypsum, and city waste compost addition affect P dynamics in saline-sodic soils - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Rajender Kumar Yadav; Parbodh Chander Sharma (Environmental Research, 2023)

Association of underlying comorbidities and progression of COVID-19 infection amongst 2586 patients hospitalised in the National Capital Region of India: a retrospective cohort study - Rashmi Rana; Vivek Ranjan; Naveen Kumar; Parul Chugh; Kamini Khillan; Atul Gogia; Devinder Singh Rana; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2023)

Design, synthesis, and biological evaluation of 2, 4-dichlorophenoxyacetamide chalcone hybrids as potential c-Met kinase inhibitors - Heena Bhojwani; Sanskruti Patil; Urmila Joshi; Vikrant Bhor; Parul Bedi (Medicinal Chemistry Research, 2023)

Assessment of mangrove cover dynamics and its health status in the Gulf of Khambhat, Western India, using high-resolution multi-temporal satellite data and Google Earth Engine - Jigarkumar B. Solanki; Nikhil Lele; Anup Kumar Das; Parul Maurya; Rina Kumari (Environmental Monitoring and Assessment, 2022)

Molecular cytogenetic analysis of novel wheat-rye translocation lines and their characterization for drought tolerance and yellow rust resistance - Parul Sharma; Harinder Kumar Chaudhary; Chandan Kapoor; N. V. Manoj; Kritika Singh; Vinod Kumar Sood (Cereal Research Communications, 2022)

Critical factors governing the efficient direct organogenesis in green-fleshed kiwifruit (Actinidia deliciosa) [A. Chev.] var. deliciosa - Deeksha Thakur; Parul Sharma; Rajnish Sharma; Chanchal Kumari; Vishal Singh Rana (In Vitro Cellular & Developmental Biology - Plant, 2022)

Species influenced growth, biomass allocation and productivity in wastewater irrigated plants in sandy soils of Indian desert - G. Singh; P. R. Nagora; Parul Haksar; Abha Rani (Irrigation Science, 2022)

Toxicity, Environmental Monitoring and Removal Strategies of Arsenic - Akshay Pawar; Simranjeet Singh; Praveen Chandra Ramamurthy; Amith G. Anil; Nabila Shehata; Daljeet Singh Dhanjal; Tandreborekaval Swamy Sunil Kumar Naik; Parul Parihar; Ram Prasad; Joginder Singh (International Journal of Environmental Research, 2022)

Role of Ubiquitin–Proteasome and Autophagy-Lysosome Pathways in α-Synuclein Aggregate Clearance - Subhashree Sahoo; Amrita Arpita Padhy; Varsha Kumari; Parul Mishra (Molecular Neurobiology, 2022)

Glyphosate-resistant Brassica juncea (oilseed mustard) transgenics for possible control of root parasite Orobanche aegyptiaca and conservation agriculture - Parul Agarwal; Arundhati Mukhopadhyay; Vibha Gupta; Akshay Kumar Pradhan; Deepak Pental (Journal of Plant Biochemistry and Biotechnology, 2022)

Salicylic acid ameliorates zinc and chromium-induced stress responses in wheat seedlings: a biochemical and computational analysis - Muhammed Khairujjaman Mazumder; Parul Sharma; Debojyoti Moulick; Sandeep Kumar Tata; Shuvasish Choudhury (Cereal Research Communications, 2022)

Differential shear wave attenuation property of the Kumaon and Garhwal Himalaya, India in terms of shallow shear wave velocity profiles - Parul Bhardwaj; A Joshi; Mohit Pandey; Mrityunjay Bhargav (Journal of Earth System Science, 2022)

Role of Endophytes in Abiotic Stress Tolerance: With Special Emphasis on Serendipita indica - Jaagriti Tyagi; Parul Chaudhary; Arti Mishra; Mahak Khatwani; Srijita Dey; Ajit Varma (International Journal of Environmental Research, 2022)

Preference of generalist predator, Eocanthecona furcellata (Wolff.) (Heteroptera: Pentatomidae) against live and larval extracts of three different insect pests - Devyani Chaudhary; R. P. Maurya; Parul Dobhal; Parul Suyal; M. Sreedhar; Radha Koranga (International Journal of Tropical Insect Science, 2022)

Characterization and ecotoxicological risk assessment of sewage sludge from industrial and non-industrial cities - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Sandeep Bedwal; Gajender Yadav; Rajender Kumar Yadav; Parbodh Chander Sharma (Environmental Science and Pollution Research, 2022)

Biomass Allocation and Productivity of Tree Seedlings in Responses to Soil Chemical Changes Under Treated Wastewater Irrigation in Indian Desert - G. Singh; P. R. Nagora; Parul Haksar; Abha Rani (Water, Air, & Soil Pollution, 2022)

Environment dependent expression of mycobacterium hormone sensitive lipases: expression pattern under ex-vivo and individual in-vitro stress conditions in M. tuberculosis H37Ra - Stuti Arya; Parul Singh; Jashandeep Kaur; Arbind Kumar; Jagdeep Kaur (Molecular Biology Reports, 2022)

In Vitro Evaluation of Insulin Release from Chitosan-Alginate Macrobeads - Ashwini Kumar; Parul Thakur; Awanish Kumar (Journal of Pharmaceutical Innovation, 2022)

Estimating regional-scale daytime net surface radiation in cloudless skies from GEO-LEO satellite observations using data fusion approach - Dhwanilnath Gharekhan; Rahul Nigam; Bimal K Bhattacharya; Devansh Desai; Parul Patel (Journal of Earth System Science, 2022)

Physiological response of maize plants and its rhizospheric microbiome under the influence of potential bioinoculants and nanochitosan - Upasana Agri; Parul Chaudhary; Anita Sharma; Bharti Kukreti (Plant and Soil, 2022)

RETRACTED ARTICLE: Guanabenz mitigates the neuropathological alterations and cell death in Alzheimer’s disease - Abhishek Singh; Parul Gupta; Shubhangini Tiwari; Amit Mishra; Sarika Singh (Cell and Tissue Research, 2022)

Neural Network-Based Prediction Model for Evaporation Using Weather Data - Kamal Batra; Parul Gandhi (Agricultural Research, 2022)

Managing arsenic (V) toxicity by phosphate supplementation in rice seedlings: modulations in AsA-GSH cycle and other antioxidant enzymes - Rohit Kumar Mishra; Gitanjali Mishra; Rachana Singh; Parul Parihar; Jitendra Kumar; Prabhat Kumar Srivastava; Sheo Mohan Prasad (Environmental Science and Pollution Research, 2022)

Short and Medium Range Forecast of Soil Moisture for the Different Climatic Regions of India Using Temporal Networks - Riya Dutta; Rajib Maity; Parul Patel (Water Resources Management, 2022)

Unrevealing metabolomics for abiotic stress adaptation and tolerance in plants - Shuvasish Choudhury; Parul Sharma; Debojyoti Moulick; Muhammed Khairujjaman Mazumder (Journal of Crop Science and Biotechnology, 2021)

Plant growth promoting Bacillus-based bio formulations improve wheat rhizosphere biological activity, nutrient uptake and growth of the plant - Priyanka Chandra; Rinki Khobra; Parul Sundha; Rakesh Kumar Sharma; Poonam Jasrotia; Amaresh Chandra; Devendra Pal Singh; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2021)

An Integrated Approach of the Potential Underlying Molecular Mechanistic Paradigms of SARS-CoV-2-Mediated Coagulopathy - Anmol Goyal; Rajendra Prasad; Parul Goel; Amit Pal; Suvarna Prasad; Isha Rani (Indian Journal of Clinical Biochemistry, 2021)

Chlorpyrifos degradation using binary fungal strains isolated from industrial waste soil - Ashish Kumar; Anita Sharma; Parul Chaudhary; Saurabh Gangola (Biologia, 2021)

Effects of ambient air pollution on emergency room visits of children for acute respiratory symptoms in Delhi, India - Rashmi Yadav; Aditya Nagori; Aparna Mukherjee; Varinder Singh; Rakesh Lodha; Sushil Kumar Kabra; Geetika Yadav; Jitendra Kumar Saini; Kamal Kumar Singhal; Kana Ram Jat; Karan Madan; Mohan P. George; et al. (Environmental Science and Pollution Research, 2021)

The enhanced phosphorus use efficiency in phosphate-deficient and mycorrhiza-inoculated barley seedlings involves activation of different sets of PHT1 transporters in roots - Rajat Srivastava; Parul Sirohi; Harsh Chauhan; Rahul Kumar (Planta, 2021)

Differential regulation of drought stress by biological membrane transporters and channels - Simranjeet Singh; Vijay Kumar; Parul Parihar; Daljeet Singh Dhanjal; Rachana Singh; Praveen C. Ramamurthy; Ram Prasad; Joginder Singh (Plant Cell Reports, 2021)

Assessment of non-point source of pollution using chemical mass balance approach: a case study of River Alaknanda, a tributary of River Ganga, India - M. K. Sharma; Pradeep Kumar; Kunarika Bhanot; Parul Prajapati (Environmental Monitoring and Assessment, 2021)

Interpreting HbA1c in Presence of Deficiency Anemias - Seema Bhargava; Khageshwar Mahato; Anjali Manocha; Mamta Kankra; Parul Singla; Anisha Sharma; Ashok Ahirwar; Vinod Gupta; Salamma Jose (Indian Journal of Clinical Biochemistry, 2021)

Prediction and identification of T cell epitopes of COVID-19 with balanced cytokine response for the development of peptide based vaccines - Medha; Parul Bhatt; Priyanka; Monika Sharma; Sadhna Sharma (In Silico Pharmacology, 2021)

Molecular cloning, expression and in-silico characterization of rosmarinic acid synthase from Ocimum tenuiflorum L. - Manish Kumar Suthar; Parul M. Purohit; Parmeshwar Lal Saran (Journal of Plant Biochemistry and Biotechnology, 2021)

A novel lincRNA identified in buffalo oocytes with protein binding characteristics could hold the key for oocyte competence - Sunny Dholpuria; Sandeep Kumar; Manish Kumar; Parul Sarwalia; Rakesh Kumar; Tirtha Kumar Datta (Molecular Biology Reports, 2021)

Cardiac complications of COVID-19: the concealed realities - Prabhu Dutta Shaw; Arathi P. Rao; Parul Malik (Infectious Diseases, 2021)

Mining histone methyltransferases and demethylases from whole genome sequence - Parul Gulati; Surbhi Kohli; Ankita Narang; Vani Brahmachari (Journal of Biosciences, 2020)

Distorted frequency of dendritic cells and their associated stimulatory and inhibitory markers augment the pathogenesis of pemphigus vulgaris - Dayasagar Das; Ashu Singh; Parul Singh Antil; Divya Sharma; Sudheer Arava; Sujay Khandpur; Alpana Sharma (Immunologic Research, 2020)

Short-chain dehydrogenase/reductase, PsDeHase, from opium poppy: putative involvement in papaverine biosynthesis - Parul Agarwal; Sumya Pathak; Ravi Shankar Kumar; Yogeshwar Vikram Dhar; Sudhir Shukla; Mehar Hasan Asif; Prabodh Kumar Trivedi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Computational analysis of a 9D model for a small DRG neuron - Parul Verma; Achim Kienle; Dietrich Flockerzi; Doraiswami Ramkrishna (Journal of Computational Neuroscience, 2020)

Overexpression of wheat transcription factor (TaHsfA6b) provides thermotolerance in barley - Anuj Kumar Poonia; Sumit Kumar Mishra; Parul Sirohi; Reeku Chaudhary; Meenakshi Kanwar; Hugo Germain; Harsh Chauhan (Planta, 2020)

Application of Pharmacokinetic-Pharmacodynamic Modeling to Inform Translation of In Vitro NaV1.7 Inhibition to In Vivo Pharmacological Response in Non-human Primate - Jeanine E. Ballard; Parul Pall; Joshua Vardigan; Fuqiang Zhao; Marie A. Holahan; Richard Kraus; Yuxing Li; Darrell Henze; Andrea Houghton; Christopher S. Burgey; Christopher Gibson (Pharmaceutical Research, 2020)
Purpose This work describes a staged approach to the application of pharmacokinetic-pharmacodynamic (PK-PD) modeling in the voltage-gated sodium ion channel (NaV1.7) inhibitor drug discovery effort to address strategic questions regarding in vitro to in vivo translation of target modulation. Methods PK-PD analysis was applied to data from a functional magnetic resonance imaging (fMRI) technique to non-invasively measure treatment mediated inhibition of olfaction signaling in non-human primates (NHPs). Initial exposure-response was evaluated using single time point data pooled across 27 compounds to inform on in vitro to in vivo correlation (IVIVC). More robust effect compartment PK-PD modeling was conducted for a subset of 10 compounds with additional PD and PK data to characterize hysteresis. Results The pooled compound exposure-response facilitated an early exploration of IVIVC with a limited dataset for each individual compound, and it suggested a 2.4-fold in vitro to in vivo scaling factor for the NaV1.7 target. Accounting for hysteresis with an effect compartment PK-PD model as compounds advanced towards preclinical development provided a more robust determination of in vivo potency values, which resulted in a statistically significant positive IVIVC with a slope of 1.057 ± 0.210, R-squared of 0.7831, and p value of 0.006. Subsequent simulations with the PK-PD model informed the design of anti-nociception efficacy studies in NHPs. Conclusions A staged approach to PK-PD modeling and simulation enabled integration of in vitro NaV1.7 potency, plasma protein binding, and pharmacokinetics to describe the exposure-response profile and inform future study design as the NaV1.7 inhibitor effort progressed through drug discovery.

Cyclodextrin-based nanostructured materials for sustainable water remediation applications - Pratibha Kumari; Parul Singh; Anchal Singhal; Alka . (Environmental Science and Pollution Research, 2020)

Assessing the robust growth and lipid-accumulating characteristics of Scenedesmus sp. for biodiesel production - Neha Arora; Shweta Tripathi; Parul Aggarwal Pruthi; Krishna Mohan Poluri; Vikas Pruthi (Environmental Science and Pollution Research, 2020)

Spatial variations of heavy metal contamination and associated risks around an unplanned landfill site in India - Parul Johar; Divya Singh; Arun Kumar (Environmental Monitoring and Assessment, 2020)

Synergistic action of indole acetic acid with homobrassinolide in easing the NaCl-induced toxicity in Solanum melongena L. seedlings - Aman Deep Raju; Parul Parihar; Rachana Singh; Jitendra Kumar; Sheo Mohan Prasad (Acta Physiologiae Plantarum, 2020)

The Hemolyzed Sample: To Analyse Or Not To Analyse - Seema Bhargava; Parul Singla; Anjali Manocha; Mamta Kankra; Anisha Sharma; Ashok Ahirwar; Rachna Ralhan; Udhavananda Thapliyal; Preet Mehra (Indian Journal of Clinical Biochemistry, 2020)

In-Silico Prediction of Peptide Based Vaccine Against Zika Virus - Parul Sharma; Rajbir Kaur; Atul Kumar Upadhyay; Vikas Kaushik (International Journal of Peptide Research and Therapeutics, 2020)

Interaction between Piriformospora indica and Azotobacter chroococcum diminish the effect of salt stress in Artemisia annua L. by enhancing enzymatic and non-enzymatic antioxidants - Monika Arora; Parul Saxena; M. Z. Abdin; Ajit Varma (Symbiosis, 2020)

Nanotechnology in sustainable agriculture: studies from seed priming to post-harvest management - Parul Shukla; Parul Chaurasia; Kaiser Younis; Ovais Shafiq Qadri; Soban Ahmad Faridi; Gaurav Srivastava (Nanotechnology for Environmental Engineering, 2019)

Correction to: Regulation of miR-34 Family in Neuronal Development - Abhishek Jauhari; Tanisha Singh; Parul Singh; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2019)

3′O-Methyltransferase, Ps3′OMT, from opium poppy: involvement in papaverine biosynthesis - Parul Agarwal; Sumya Pathak; Ravi Shankar Kumar; Yogeshwar Vikram Dhar; Ashutosh Pandey; Sudhir Shukla; Prabodh Kumar Trivedi (Plant Cell Reports, 2019)

Genome-wide identification and expression profiling of genes encoding universal stress proteins (USP) identify multi-stress responsive USP genes in Arabidopsis thaliana - Monika Bhuria; Parul Goel; Sanjay Kumar; Anil Kumar Singh (Plant Physiology Reports, 2019)

Suppression of aerosol-induced atmospheric warming by clouds in the Indo-Gangetic Basin, northern India - Parul Srivastava; Sagnik Dey; Atul Kumar Srivastava; Sachchidanand Singh; Suresh Tiwari (Theoretical and Applied Climatology, 2019)

Non-HDL as a Valid Surrogate Marker of Small Dense LDL in a Young Indian Population - Anjali Manocha; Seema Bhargava; Rajneesh Jain; Mamta Kankra; Parul Singla; Parul Chugh (Indian Journal of Clinical Biochemistry, 2019)

Direct Shoot Organogenesis from Seedling Derived Shoot Tip Explants of Endangered Medicinal Plant Saussurea costus (Falc.) Lipsch. - Sneh Sharma; Rajnish Sharma; Parul Sharma; Kalpna Thakur; Bhupender Dutt (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Evaluating the effect of codon optimization on expression of bar gene in transgenic tobacco plants - Parul Agarwal; Taru Gautam; Amarjeet Kumar Singh; Pradeep Kumar Burma (Journal of Plant Biochemistry and Biotechnology, 2019)

Co-culturing of oleaginous microalgae and yeast: paradigm shift towards enhanced lipid productivity - Neha Arora; Alok Patel; Juhi Mehtani; Parul A Pruthi; Vikas Pruthi; Krishna Mohan Poluri (Environmental Science and Pollution Research, 2019)

An apple transcription factor, MdDREB76, confers salt and drought tolerance in transgenic tobacco by activating the expression of stress-responsive genes - Vishal Sharma; Parul Goel; Sanjay Kumar; Anil Kumar Singh (Plant Cell Reports, 2019)

Genome-wide analysis of oligopeptide transporters and detailed characterization of yellow stripe transporter genes in hexaploid wheat - Anil Kumar; Gazaldeep Kaur; Parul Goel; Kaushal Kumar Bhati; Mandeep Kaur; Vishnu Shukla; Ajay Kumar Pandey (Functional & Integrative Genomics, 2019)

Potential of aquatic oomycete as a novel feedstock for microbial oil grown on waste sugarcane bagasse - Alok Patel; Leonidas Matsakas; Parul A Pruthi; Vikas Pruthi (Environmental Science and Pollution Research, 2018)

Little imaginal discs, a Trithorax group member, is a constituent of nuclear matrix of Drosophila melanogaster embryos - Parul Varma; Rakesh K Mishra (Journal of Biosciences, 2018)

Glycogen Synthase Kinase-3β Regulates Equilibrium Between Neurogenesis and Gliogenesis in Rat Model of Parkinson’s Disease: a Crosstalk with Wnt and Notch Signaling - Sonu Singh; Akanksha Mishra; Sachi Bharti; Virendra Tiwari; Jitendra Singh; Parul; Shubha Shukla (Molecular Neurobiology, 2018)

Interaction between Piriformospora indica and Azotobacter chroococcum governs better plant physiological and biochemical parameters in Artemisia annua L. plants grown under in vitro conditions - Monika Arora; Parul Saxena; M. Z. Abdin; Ajit Varma (Symbiosis, 2018)

In praise of mealybugs - Vani Brahmachari; Surbhi Kohli; Parul Gulati (Journal of Genetics, 2018)

Evaluation of Genetic Relatedness Among Temperate Pome Fruit Crops of Family Rosaceae Using Arbitrary Oligonucleotide Markers - Himani Sharma; Parul Sharma; Rajnish Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Regulation of miR-34 Family in Neuronal Development - Abhishek Jauhari; Tanisha Singh; Parul Singh; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2018)

Amaranth seeds (Amaranthus palmeri L.) as novel feedstock for biodiesel production by oleaginous yeast - Farha Deeba; Alok Patel; Neha Arora; Vikas Pruthi; Parul A. Pruthi; Yuvraj S. Negi (Environmental Science and Pollution Research, 2018)

Gut microbiome contributes to impairment of immunity in pulmonary tuberculosis patients by alteration of butyrate and propionate producers - Abhijit Maji; Richa Misra; Darshan B. Dhakan; Vipin Gupta; Nitish K. Mahato; Rituja Saxena; Parul Mittal; Nitin Thukral; Eshan Sharma; Anoop Singh; Richa Virmani; Mohita Gaur; et al. (Environmental Microbiology, 2018)
Summary Tuberculosis (TB) is primarily associated with decline in immune health status. As gut microbiome (GM) is implicated in the regulation of host immunity and metabolism, here we investigate GM alteration in TB patients by 16S rRNA gene and whole‐genome shotgun sequencing. The study group constituted of patients with pulmonary TB and their healthy household contacts as controls (HCs). Significant alteration of microbial taxonomic and functional capacity was observed in patients with active TB as compared to the HCs. We observed that Prevotella and Bifidobacterium abundance were associated with HCs, whereas butyrate and propionate‐producing bacteria like Faecalibacterium , Roseburia , Eubacterium and Phascolarctobacterium were significantly enriched in TB patients. Functional analysis showed reduced biosynthesis of vitamins and amino acids in favour of enriched metabolism of butyrate and propionate in TB subjects. The TB subjects were also investigated during the course of treatment, to analyse the variation of GM. Although perturbation in microbial composition was still evident after a month's administration of anti‐TB drugs, significant changes were observed in metagenome gene pool that pointed towards recovery in functional capacity. Therefore, the findings from this pilot study suggest that microbial dysbiosis may contribute to pathophysiology of TB by enhancing the anti‐inflammatory milieu in the host.

RNAi-mediated modulation of squalene synthase gene expression in Artemisia annua L. and its impact on artemisinin biosynthesis - Athar Ali; Malik Mobeen Ahmad; Mather Ali Khan; Parul Saxena; Shazia Khan; Malik Zainul Abdin (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Plant growth promoting activities of rhizobacteria isolated from Podophyllum hexandrum growing in North-West regions of the Himalaya - Rashmi Sharma; Parul Sharma; Anjali Chauhan; Abhishek Walia; C. K. Shirkot (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Molecular Modeling of Cloned Bacillus subtilis Keratinase and Its Insinuation in Psoriasis Treatment Using Docking Studies - Sonali Gupta; Parul Tewatia; Jyoti Misri; Rajni Singh (Indian Journal of Microbiology, 2017)

Differentiation Induces Dramatic Changes in miRNA Profile, Where Loss of Dicer Diverts Differentiating SH-SY5Y Cells Toward Senescence - Abhishek Jauhari; Tanisha Singh; Ankita Pandey; Parul Singh; Nishant Singh; Ankur Kumar Srivastava; Aditya Bhushan Pant; Devendra Parmar; Sanjay Yadav (Molecular Neurobiology, 2017)

Comprehensive assessment of the genes involved in withanolide biosynthesis from Withania somnifera: chemotype-specific and elicitor-responsive expression - Aditya Vikram Agarwal; Parul Gupta; Deeksha Singh; Yogeshwar Vikram Dhar; Deepak Chandra; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2017)

The Drosophila bipectinata species complex: phylogenetic relationship among different members based on chromosomal variations - PARUL BANERJEE; BASHISTH N. SINGH (Journal of Genetics, 2017)

Gene expression analysis of the withanolide biosynthetic pathway in hairy root cultures of Withania somnifera elicited with methyl jasmonate and the fungus Piriformospora indica - Parul Saxena; Seema Ahlawat; Athar Ali; Shazia Khan; Malik Zainul Abdin (Symbiosis, 2017)

Anti-nociceptive effect of some synthesized smaller chain tripeptides and tetrapeptides in mice - Kandasamy Nagarajan; Vinay Kumar; Parul Grover; Roma Ghai; Pritesh Kumar Rai; Shamshir Alam; Umakant Bajaj (Medicinal Chemistry Research, 2016)

Bioremediation of domestic and industrial wastewaters integrated with enhanced biodiesel production using novel oleaginous microalgae - Neha Arora; Alok Patel; Km Sartaj; Parul A. Pruthi; Vikas Pruthi (Environmental Science and Pollution Research, 2016)

Impact of oxidative and osmotic stresses on Candida albicans biofilm formation - Suma C. Pemmaraju; Kumar Padmapriya; Parul A. Pruthi; R. Prasad; Vikas Pruthi (Biofouling, 2016)

Genome-wide characterization and expression profiling of TIFY gene family in pigeonpea (Cajanus cajan (L.) Millsp.) under copper stress - Geetika Sirhindi; Poonam Sharma; Preeti Arya; Parul Goel; Gulshan Kumar; Vishal Acharya; Anil Kumar Singh (Journal of Plant Biochemistry and Biotechnology, 2016)

A Preliminary Estimate of Total Petroleum Hydrocarbons in Water and Some Commercially Important Fish Species in the Amba Estuary, West Coast of India - M. Nageswar Rao; Anirudh Ram; M. A. Rokade; P. Raja; P. S. Rakesh; Parul Chemburkar; S. N. Gajbhiye (Bulletin of Environmental Contamination and Toxicology, 2016)

Modulation of Candida albicans Biofilm by Different Carbon Sources - Suma C. Pemmaraju; Parul A. Pruthi; R. Prasad; Vikas Pruthi (Mycopathologia, 2016)

Comparative analysis of transcription factor gene families from Papaver somniferum: identification of regulatory factors involved in benzylisoquinoline alkaloid biosynthesis - Parul Agarwal; Sumya Pathak; Deepika Lakhwani; Parul Gupta; Mehar Hasan Asif; Prabodh Kumar Trivedi (Protoplasma, 2016)

The Drosophila bipectinata species complex: degree of sterility and dystrophied ovaries in interspecific hybrid females - PARUL BANERJEE; BASHISTH N. SINGH (Journal of Genetics, 2016)

Dual symbiosis between Piriformospora indica and Azotobacter chroococcum enhances the artemisinin content in Artemisia annua L. - Monika Arora; Parul Saxena; Devendra Kumar Choudhary; Malik Zainul Abdin; Ajit Varma (World Journal of Microbiology and Biotechnology, 2016)

UV-B induces biomass production and nonenzymatic antioxidant compounds in three cyanobacteria - Jitendra Kumar; Parul Parihar; Rachana Singh; Vijay Pratap Singh; Sheo Mohan Prasad (Journal of Applied Phycology, 2016)

Genome- wide characterization of Nuclear Factor Y (NF-Y) gene family of sorghum [Sorghum bicolor (L.) Moench]: a bioinformatics approach - Neha Malviya; Parul Jaiswal; Dinesh Yadav (Physiology and Molecular Biology of Plants, 2016)

Sex-specific asymmetry in eye development in interspecific hybrids in the Drosophila bipectinata species complex - BASHISTH N. SINGH; PARUL BANERJEE (Journal of Genetics, 2015)

Interspecific hybridization does not affect the level of fluctuating asymmetry (FA) in the Drosophila bipectinata species complex - Parul Banerjee; B. N. Singh (Genetica, 2015)

An approach to validate soil moisture derived from passive microwave sensors using SAR as an interface - Parul Patel; Hari Shanker Srivastava (International Journal of Remote Sensing, 2015)

Effect of salinity stress on plants and its tolerance strategies: a review - Parul Parihar; Samiksha Singh; Rachana Singh; Vijay Pratap Singh; Sheo Mohan Prasad (Environmental Science and Pollution Research, 2015)

Hypoglycemic herbs and their polyherbal formulations: a comprehensive review - Deepti Katiyar; Vijender Singh; Sadaf J. Gilani; Richa Goel; Parul Grover; Amita Vats (Medicinal Chemistry Research, 2015)

Aerosol characteristics over Delhi national capital region: a satellite view - Parul Srivastava; Sagnik Dey; P. Agarwal; George Basil (International Journal of Remote Sensing, 2014)

Conservation of PHO pathway in ascomycetes and the role of Pho84 - Parul Tomar; Himanshu Sinha (Journal of Biosciences, 2014)

Methane oxidation and abundance of methane oxidizers in tropical agricultural soil (vertisol) in response to CuO and ZnO nanoparticles contamination - Santosh Ranjan Mohanty; Parul Rajput; Bharati Kollah; Dipanti Chourasiya; Archana Tiwari; Muneshwar Singh; A Subba Rao (Environmental Monitoring and Assessment, 2014)

Trojan Genes or Transparent Genomes? Sexual Selection and Potential Impacts of Genetically Modified Animals in Natural Ecosystems - C. David Rollo; Aarti Kumar; Richard Smith; Jiaxi Wang; Vadim Aksenov; Jiawei Han; Parul Khanna (Evolutionary Biology, 2014)

A study on the influence of different promoter and 5′UTR (URM) cassettes from Arabidopsis thaliana on the expression level of the reporter gene β glucuronidase in tobacco and cotton - Parul Agarwal; Varsha Garg; Taru Gautam; Beena Pillai; Shaveta Kanoria; Pradeep Kumar Burma (Transgenic Research, 2014)

Exploring QSAR studies on 4-substituted quinazoline derivatives as antimalarial compounds for the development of predictive models - Mitali Mishra; Vikash Kumar Mishra; Parul Senger; Anupam Kumar Pathak; Sushil K. Kashaw (Medicinal Chemistry Research, 2014)

The GATA and SORLIP motifs in the 3-hydroxy-3-methylglutaryl-CoA reductase promoter of Picrorhiza kurrooa for the control of light-mediated expression - Tabasum Kawoosa; Parul Gahlan; Aribam Surbala Devi; Sanjay Kumar (Functional & Integrative Genomics, 2014)

Natural mutations in two homoeologous TT8 genes control yellow seed coat trait in allotetraploid Brassica juncea (AABB) - Lakshmi K. Padmaja; Parul Agarwal; Vibha Gupta; Arundhati Mukhopadhyay; Yaspal S. Sodhi; Deepak Pental; Akshay K. Pradhan (Theoretical and Applied Genetics, 2014)

Naturally occurring neuronal plasticity in visual wulst of the Baya weaver, Ploceus philippinus (Linnaeus, 1766) - U. C. Srivastava; Parul Gaur (Cell and Tissue Research, 2013)

Cloning and functional characterization of 3-hydroxy-3-methylglutaryl coenzyme A reductase gene from Withania somnifera: an important medicinal plant - Nehal Akhtar; Parul Gupta; Neelam Singh Sangwan; Rajender Singh Sangwan; Prabodh Kumar Trivedi (Protoplasma, 2013)

Cloning and characterization of 2-C-methyl-d-erythritol-4-phosphate pathway genes for isoprenoid biosynthesis from Indian ginseng, Withania somnifera - Parul Gupta; Aditya Vikram Agarwal; Nehal Akhtar; Rajender Singh Sangwan; Surya Pratap Singh; Prabodh Kumar Trivedi (Protoplasma, 2013)

Antifertility activity of methanolic bark extract of Aegle marmelos (l.) in male wistar rats - Shyam S Agrawal; Ashok Kumar; Sumeet Gullaiya; Vishal Dubey; Ashish Nagar; Poonam Tiwari; Parul Dhar; Varun Singh (DARU Journal of Pharmaceutical Sciences, 2012)

Erratum to: Sterol glycosyltransferases-identification of members of gene family and their role in stress in Withania somnifera - Pankaj Chaturvedi; Manoj Mishra; Nehal Akhtar; Parul Gupta; Pratibha Misra; Rakesh Tuli (Molecular Biology Reports, 2012)

Sterol glycosyltransferases-identification of members of gene family and their role in stress in Withania somnifera - Pankaj Chaturvedi; Manoj Mishra; Nehal Akhtar; Parul Gupta; Pratibha Mishra; Rakesh Tuli (Molecular Biology Reports, 2012)

Free Radical Status in Retinopathy of Prematurity - Upma Garg; Anju Jain; Parul Singla; Sarita Beri; Rajiv Garg; Arvind Saili (Indian Journal of Clinical Biochemistry, 2012)

Fungicide impacts on photosynthesis in crop plants - Anne-Noëlle Petit; Florence Fontaine; Parul Vatsa; Christophe Clément; Nathalie Vaillant-Gaveau (Photosynthesis Research, 2012)

CO-Kriging Approach for Cartosat-1 Height Product with ICESat/GLAS Data for Digital Elevation Surface Generation - Anil Kumar; Parul Trivedi (Journal of the Indian Society of Remote Sensing, 2012)

Interspecific sexual isolation and phylogeny among different members of the Drosophila bipectinata species complex - Parul Banerjee; Bashisth N. Singh (Genetica, 2012)

Regeneration of Red Cell Cholinesterase Activity Following Pralidoxime (2-PAM) Infusion in First 24 h in Organophosphate Poisoned Patients - Parul Goel; Nidhi Gupta; Surjit Singh; Ashish Bhalla; Navneet Sharma; K. D. Gill (Indian Journal of Clinical Biochemistry, 2012)

Lithostratigraphic development and neotectonic significance of the Quaternary sediments along the Kachchh Mainland Fault (KMF) zone, western India - V CHOWKSEY; D M MAURYA; PARUL JOSHI; N KHONDE; ARCHANA DAS; L S CHAMYAL (Journal of Earth System Science, 2011)

Dynamics of nuclear matrix proteome during embryonic development in Drosophila melanogaster - Parul Varma; Rakesh K Mishra (Journal of Biosciences, 2011)

Genetic diversity and relationships among germplasm of Jatropha curcas L. revealed by RAPDs - R. V. Kumar; Yogendra K. Tripathi; Parul Shukla; S. P. Ahlawat; V. K. Gupta (Trees, 2009)

Single-nucleotide variations associated with Mycobacterium tuberculosis KwaZulu-Natal strains - Sarbashis Das; Ragothaman M. Yennamalli; Anchal Vishnoi; Parul Gupta; Alok Bhattacharya (Journal of Biosciences, 2009)

Regional genomic instability predisposes to complex dystrophin gene rearrangements - Junko Oshima; Daniel B. Magner; Jennifer A. Lee; Amy M. Breman; Eric S. Schmitt; Lisa D. White; Carol A. Crowe; Michelle Merrill; Parul Jayakar; Aparna Rajadhyaksha; Christine M. Eng; Daniela del Gaudio (Human Genetics, 2009)

Post-harvest decline in commerical cane sugar and its relationship with quality parameters in sugarcane under sub-tropical climate - Parul Srivastava; C. Chatterjee; A. K. Shrivastava; S. Solomon; A. K. Srivastava; B. K. Dube (Sugar Tech, 2009)

Biofilm formation by Candida albicans isolated from intrauterine devices - Priyanka Lal; Vishnu Agarwal; Parul Pruthi; Ben M. J. Pereira; M. R. Kural; Vikas Pruthi (Indian Journal of Microbiology, 2008)

Cell Cycle Stage Specific Application of Cypermethrin and Carbendazim to Assess the Genotoxicity in Somatic Cells of Hordeum Vulgare L - Parul Singh; Anjil Kumar Srivastava; Ashok Kumar Singh (Bulletin of Environmental Contamination and Toxicology, 2008)

Influence of progressive staling on germination of sugarcane - A. K. Shrivastava; S. Solomon; A. K. Srivastava; S. P. Shukla; A. Sawnani; R. Darash; C. Prajapati; Pushpa Singh; Priyanka Singh; R. K. Rai; R. Jain; Parul Srivastava; et al. (Sugar Tech, 2008)

CNTO 95, a fully human anti αv integrin antibody, inhibits cell signaling, migration, invasion, and spontaneous metastasis of human breast cancer cells - Qiming Chen; Carol D. Manning; Hillary Millar; Francis L. McCabe; Catherine Ferrante; Celia Sharp; Lillian Shahied-Arruda; Parul Doshi; Marian T. Nakada; G. Mark Anderson (Clinical & Experimental Metastasis, 2008)

Rearrangement of the JC virus regulatory region sequence in the bone marrow of a patient with rheumatoid arthritis and progressive multifocal leukoencephalopathy - Angela Marzocchetti; Christian Wuthrich; Chen S Tan; Troy Tompkins; Francisco Bernal-Cano; Parul Bhargava; Allan H Ropper; Igor J Koralnik (Journal of NeuroVirology, 2008)

Constitutive overexpression of a stress-inducible small GTP-binding protein PgRab7 from Pennisetum glaucum enhances abiotic stress tolerance in transgenic tobacco - Pradeep K. Agarwal; Parinita Agarwal; Parul Jain; Bhavanath Jha; M. K. Reddy; S. K. Sopory (Plant Cell Reports, 2007)

Stms Marker for Tagging High Sugar Genes in Sugarcane - R. K. Singh; Parul Singh; Pragati Misra; Sudhir Pratap Singh; S. B. Singh (Sugar Tech, 2005)

Sequence analysis of the long arm of rice chromosome 11 for rice?wheat synteny - Saurabh Raghuvanshi; Subodh K. Srivastava; Anupama Gaur; Ajit K. Pal; Vivek Dalal; Archana Singh; Irfan A. Ghazi; Ashutosh Bhargav; Mahavir Yadav; Anupam Dixit; Kamlesh Batra; Kishor Gaikwad; et al. (Functional & Integrative Genomics, 2004)

Structural and functional analysis of rice genome - Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Saurabh Raghuvanshi; Anupama Gaur; Anita Kapur; Vikrant Gupta; Dibyendu Kumar; V. Ravi; Shubha Vij; Parul Khurana; Sulabha Sharma (Journal of Genetics, 2004)

Pattern of diversity for morphological and alkaloid yield related traits among the periwinkle Catharanthus roseus accessions collected from in and around Indian subcontinent - Parul Mishra; G.C. Uniyal; S. Sharma; Sushil Kumar (Genetic Resources and Crop Evolution, 2001)

Purification and characterization of trypsin inhibitor from seeds of faba bean (Vicia faba L.) - Parul Gupta; Kamal Dhawan; Sarla P Malhotra; Randhir Singh (Acta Physiologiae Plantarum, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)